Is Malaysia exchange rate misalignment before the 1997 crisis? - Lee, Chin; Mohamed, Azali; Yusop, Zulkornain; Yusoff, Mohammed (Universiti Malaysia Sabah, 2008)

(untitled)
This paper seeks to use the flexible-price monetary model in the cointegration and vector error correction model (VECM) contexts to determine whether there was misalignment in the Malaysian ringgit - U.S. dollar before the 1997 currency crisis. Unit roots, cointegration and weak exogeneity are tested to validate the monetary exchange rate model. Generally, it is found that all the series are I(1) process and there exists significant cointegrating vectors. Using the cointegrating vector and the final parsimonious VECM, out of sample predictions for Ringgit exchange rate are generated. The resulting residuals between the actual and the fitted values of exchange rate are the estimated misalignments. From cointegration, our results suggest that the Malaysian ringgit was overvalued from 1995Q2-1997Q2. Based on VECM, our results suggest that ringgit was overvalued from 1995Q2-1996Q2 and slightly undervalued from 1996Q3-1997Q2.